Answer:
y = -3/2 x +13
Step-by-step explanation:
We want our line to be perpendicular to
y = 2/3 x -1
The slope of this line is 2/3 (since it is written in the form y = mx+b and m is the slope)
Perpendicular lines have negative reciprocal slopes
m = -(3/2)
The slope of our new line is -3/2
We can use point slope form of the equation
y-y1 - m (x-x1)
y - 7 = -3/2 (x-4)
Distribute
y-7 = -3/2x +6
Add 7 to each side
y-7+7 = -3/2 x +6+7
y = -3/2 x +13
Using proportions, according to the ratio of the partition, it is found that the location of point g is at 3.
<h3>What is a proportion?</h3>
A proportion is a fraction of a total amount, and the measures are related using a rule of three.
In this problem, point g partitions the directed line segment from d to f into a 5:4 ratio, hence:
![g - d = \frac{5}{9}(f - d)](https://tex.z-dn.net/?f=g%20-%20d%20%3D%20%5Cfrac%7B5%7D%7B9%7D%28f%20-%20d%29)
We have that d = -2 and f = 7, hence:
![g - d = \frac{5}{9}(f - d)](https://tex.z-dn.net/?f=g%20-%20d%20%3D%20%5Cfrac%7B5%7D%7B9%7D%28f%20-%20d%29)
![g + 2 = \frac{5}{9}(7 + 2)](https://tex.z-dn.net/?f=g%20%2B%202%20%3D%20%5Cfrac%7B5%7D%7B9%7D%287%20%2B%202%29)
g + 2 = 5.
g = 3.
More can be learned about proportions at brainly.com/question/24372153
#SPJ4
Answer:
![tan(x)=\frac{44\sqrt{89}}{89}](https://tex.z-dn.net/?f=tan%28x%29%3D%5Cfrac%7B44%5Csqrt%7B89%7D%7D%7B89%7D)
Step-by-step explanation:
tan is defined as: ![tan(x)=\frac{opposite}{adjacent}](https://tex.z-dn.net/?f=tan%28x%29%3D%5Cfrac%7Bopposite%7D%7Badjacent%7D)
sin is defined as: ![sin(x)=\frac{opposite}{hypotenuse}](https://tex.z-dn.net/?f=sin%28x%29%3D%5Cfrac%7Bopposite%7D%7Bhypotenuse%7D)
cos is defined as: ![cos(x)=\frac{adjacent}{hypotenuse}](https://tex.z-dn.net/?f=cos%28x%29%3D%5Cfrac%7Badjacent%7D%7Bhypotenuse%7D)
We can also define tan as: ![tan(x)=\frac{sin(x)}{cos(x)}](https://tex.z-dn.net/?f=tan%28x%29%3D%5Cfrac%7Bsin%28x%29%7D%7Bcos%28x%29%7D)
because plugging in the definitions of sin and cos in we get: ![tan(x)=\frac{(\frac{opposite}{hypotenuse})}{(\frac{adjacent}{hypotenuse})}\\\\tan(x)=\frac{opposite}{hypotenuse}*\frac{hypotenuse}{adjacent}\\\\tan(x)=\frac{opposite}{adjacent}](https://tex.z-dn.net/?f=tan%28x%29%3D%5Cfrac%7B%28%5Cfrac%7Bopposite%7D%7Bhypotenuse%7D%29%7D%7B%28%5Cfrac%7Badjacent%7D%7Bhypotenuse%7D%29%7D%5C%5C%5C%5Ctan%28x%29%3D%5Cfrac%7Bopposite%7D%7Bhypotenuse%7D%2A%5Cfrac%7Bhypotenuse%7D%7Badjacent%7D%5C%5C%5C%5Ctan%28x%29%3D%5Cfrac%7Bopposite%7D%7Badjacent%7D)
which you'll notice is the original definition of tan(x)
So using this definition of tan(x) we can use the givens sin(x) and cos(x) to find tan(x)
![sin(x)=\frac{44}{45}\\\\cos(x)=\frac{\sqrt{89}}{45}\\\\tan(x)=\frac{sin(x)}{cos(x)}](https://tex.z-dn.net/?f=sin%28x%29%3D%5Cfrac%7B44%7D%7B45%7D%5C%5C%5C%5Ccos%28x%29%3D%5Cfrac%7B%5Csqrt%7B89%7D%7D%7B45%7D%5C%5C%5C%5Ctan%28x%29%3D%5Cfrac%7Bsin%28x%29%7D%7Bcos%28x%29%7D)
plugging in sin(x) and cos(x) we get:
![tan(x)=\frac{\frac{44}{45}}{\frac{\sqrt{89}}{45}}\\\\tan(x)=\frac{44}{45}*\frac{45}{\sqrt{89}}\\\\tan(x)=\frac{44}{\sqrt{89}}](https://tex.z-dn.net/?f=tan%28x%29%3D%5Cfrac%7B%5Cfrac%7B44%7D%7B45%7D%7D%7B%5Cfrac%7B%5Csqrt%7B89%7D%7D%7B45%7D%7D%5C%5C%5C%5Ctan%28x%29%3D%5Cfrac%7B44%7D%7B45%7D%2A%5Cfrac%7B45%7D%7B%5Csqrt%7B89%7D%7D%5C%5C%5C%5Ctan%28x%29%3D%5Cfrac%7B44%7D%7B%5Csqrt%7B89%7D%7D)
We usually don't like square roots in the denominator, and from here we want to rationalize the denominator which we do by removing the square root from the denominator.
We can do this by multiplying the fraction by:
which doesn't change the value of the fraction since it simplifies to 1, but it gets rid of the square root in the denominator
![tan(x)=\frac{44}{\sqrt{89}}*\frac{\sqrt{89}}{\sqrt{89}}\\\\tan(x)=\frac{44\sqrt{89}}{89}](https://tex.z-dn.net/?f=tan%28x%29%3D%5Cfrac%7B44%7D%7B%5Csqrt%7B89%7D%7D%2A%5Cfrac%7B%5Csqrt%7B89%7D%7D%7B%5Csqrt%7B89%7D%7D%5C%5C%5C%5Ctan%28x%29%3D%5Cfrac%7B44%5Csqrt%7B89%7D%7D%7B89%7D)
1/(sqrt(1+x^2))..................
Answer:
11. (x, y) -> (7, -3)
14. (x, y) -> (-3, -2)
15. (x, y) -> (-3, 2)
16. (x, y) -> (7,6)
20.(x, y) -> (4, 1)
Step-by-step explanation:
11.
x + 3y = 1
-3x -3y = -15
-2x = -14
/-2 /-2
x = 7
x + 3y = 1
7 + 3y = 1
-7 -7
3y = -6
/3 /3
y = -2
(x, y) -> (7, -3)
14.
-3x + 3y = 3
-5x + y = 13
-5x + y = 13
+5x +5x
y = 5x + 13
-3x + 3(5x + 13) = 3
-3x + 15x + 39 = 3
12x + 39 = 3
- 39 -39
12x = -36
/12 /12
x = -3
Now, we solve for y:
-5x + y = 13
-5(-3) + y = 13
15 + y = 13
-15 -15
y = -2
(x, y) -> (-3, -2)
15.
6x + 6y = -6
5x + y = -13
5x + y = -13
-5x -5x
y = -5x - 13
6x + 6y = -6
6x + 6(-5x - 13) = -6
6x -30x - 78 = -6
-24x - 78 = -6
+ 78 + 78
-24x = 72
/-24 /-24
x = -3
Now, we solve for y:
6x + 6y = -6
6x + 6y = -6
6(-3) + 6y = -6
-18 + 6y = -6
+18 +18
6y = 12
/6 /6
y = 2
(x, y) -> (-3, 2)
16.
2x + y = 20
6x - 5y = 12
2x + y = 20
-2x -2x
y = -2x + 20
6x - 5y = 12
6x - 5(-2x + 20) = 12
6x + 10x - 100 = 12
16x - 100 = 12
+ 100 +100
16x = 112
/16 /16
x = 7
Now, we solve for y:
2x + y = 20
2(7) + y = 20
14 + y = 20
-14 -14
y = 6
(x, y) -> (7,6)
20.
-2x - y = -9
5x - 2y = 18
-2x - y = -9
+2x +2x
-y = 2x - 9
/-1 /-1
y = -2x + 9
5x -2y = 18
5x - 2(-2x + 9) = 18
5x + 4x - 18 = 18
9x - 18 = 18
+ 18 + 18
9x = 36
/9 /9
x = 4
Now, we solve for y:
-2(4) - y = -9
-8 - y = -9
+ 8 +8
-y = -1
/-1 /-1
y = 1
(x, y) -> (4, 1)
Hope this helps!